Crystal structure of the FK506 binding domain of human FKBP25 in complex with FK506 - Prakash, Ajit (Protein Sci, 2016)
Human FKBP25 (hFKBP25) is a nuclear immunophilin and interacts with several nuclear proteins, hence involving in many nuclear events. Similar to other FKBPs, FK506 binding domain (FKBD) of hFKBP25 also binds to immunosuppressive drugs such as rapamycin and FK506, albeit with a lower affinity for the latter. The molecular basis underlying this difference in affinity could not be addressed due to the lack of the crystal structure of hFKBD25 in complex with FK506. Here, we report the crystal structure of hFKBD25 in complex with FK506 determined at 1.8 Å resolution and its comparison with the hFKBD25–rapamycin complex, bringing out the microheterogeneity in the mode of interaction of these drugs, which could possibly explain the lower affinity for FK506.